A evolução dos direitos das mulheres nas constituições brasileiras: (in)efetividade e perspectivas - Abrão, Isabella Yázigi (2023)
Equality between people, and therefore between men and women, has been legally guaranteed since the beginning of the Brazilian Constitutional Law, which began almost 200 years ago. However, Brazil still has several indicators of inequality between men and women and poor performance in international rankings on the subject. In the present work, it is questioned what are the causes that generate the social ineffectiveness of gender equality in Brazil. In this context, the social history and legislative evolution of women's rights are addressed, more specifically the right to education/labor, political rights and sexual/reproductive rights. It was observed that until nowadays these rights can’t be fully exercised by women, due to specific obstacles of the patriarchal system, which contributes greatly to the absence of isonomy. Therefore, this work identifies possible solutions to be adopted by the State, considering the social participation, for the effectiveness of the principle, and the perspectives about it, based on recent national and international events